How work–family enrichment influence innovative work behavior: Role of psychological capital and supervisory support. (15th May 2017) - Mishra, Pavitra; Bhatnagar, Jyotsna; Gupta, Rajen; Wadsworth, Shelley MacDermid
Abstract: This paper examines the relationship between bi-directional work–family enrichment, psychological capital, and supervisor support in promoting innovative work behavior. We hypothesized that work-to-family enrichment and family-to-work enrichment would have a positive relation with psychological capital. Further, we examined that psychological capital would mediate the relationship between (i) work-to-family enrichment and innovative work behavior, and (ii) family-to-work enrichment and innovative work behavior. We also studied the role of supervisor support as a predictor or moderator for catalyzing innovative work behavior. Data were collected through questionnaire survey from 398 service-sector employees. We analyzed the data using structural equation modeling. Building on the theoretical foundation of broaden-and-build theory, we establish that both work-to-family enrichment and family-to-work enrichment were positively related to psychological capital. Psychological capital fully mediated between bi-directional enrichment and innovative work behavior. Supervisor support was directly related to innovative work behavior. We also suggest interventions for facilitating innovative work behavior.